Energy management in pump-controlled actuators - Costa, Gustavo Koury; Sepehri, Nariman (Frontiers in Mechanical Engineering, 2024)
Pump-controlled actuators, or more generically, hydrostatic actuators, have the significant advantage of not relying on valves to control the cylinders. This results in much better energy usage compared to traditional valve-controlled systems. However, it is possible to further increase energy efficiency by storing load energy in motoring quadrants and subsequently releasing the stored energy back into the circuit or making it available for other applications. Much work is needed to practically study energy storage in hydrostatic actuators. In this note, we review the two basic ways hydraulic energy can be saved in circuits using accumulators, emphasizing their advantages and drawbacks. The review is followed by a brief description of the current research being carried out at the University of Manitoba in Canada. We aim to show that research in this field is promising and demonstrates that hydraulic power transmission can not only be made efficient but also be used to regenerate load energy that would otherwise go to waste.